Nutritional modulation of training-induced skeletal muscle adaptations - Hawley, J. A.; Burke, L. M.; Phillips, S. M.; Spriet, L. L. (Journal of Applied Physiology, 2011)
Skeletal muscle displays remarkable plasticity, enabling substantial adaptive modifications in its metabolic potential and functional characteristics in response to external stimuli such as mechanical loading and nutrient availability. Contraction-induced adaptations are determined largely by the mode of exercise and the volume, intensity, and frequency of the training stimulus. However, evidence is accumulating that nutrient availability serves as a potent modulator of many acute responses and chronic adaptations to both endurance and resistance exercise. Changes in macronutrient intake rapidly alter the concentration of blood-borne substrates and hormones, causing marked perturbations in the storage profile of skeletal muscle and other insulin-sensitive tissues. In turn, muscle energy status exerts profound effects on resting fuel metabolism and patterns of fuel utilization during exercise as well as acute regulatory processes underlying gene expression and cell signaling. As such, these nutrient-exercise interactions have the potential to activate or inhibit many biochemical pathways with putative roles in training adaptation. This review provides a contemporary perspective of our understanding of the molecular and cellular events that take place in skeletal muscle in response to both endurance and resistance exercise commenced after acute and/or chronic alterations in nutrient availability (carbohydrate, fat, protein, and several antioxidants). Emphasis is on the results of human studies and how nutrient provision (or lack thereof) interacts with specific contractile stimulus to modulate many of the acute responses to exercise, thereby potentially promoting or inhibiting subsequent training adaptation.